2012
DOI: 10.1371/journal.pone.0030154
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Action Potential Initiation in the GABAergic Thalamic Reticular Nucleus In Vivo

Abstract: Understanding the neural mechanisms of action potential generation is critical to establish the way neural circuits generate and coordinate activity. Accordingly, we investigated the dynamics of action potential initiation in the GABAergic thalamic reticular nucleus (TRN) using in vivo intracellular recordings in cats in order to preserve anatomically-intact axo-dendritic distributions and naturally-occurring spatiotemporal patterns of synaptic activity in this structure that regulates the thalamic relay to ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 51 publications
4
25
0
Order By: Relevance
“…Moreover, in vitro recordings from TRN neurons showed that spindle-like photostimuli could reliably evoke repetitive burst firing activity, which is comparable to the rhythmic spike-burst activity of TRN neurons (5,23,24). This is an intrinsic firing pattern of TRN neurons during NREM sleep and is hypothesized to be the main factor that drives generation of sleep spindles (4,23).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, in vitro recordings from TRN neurons showed that spindle-like photostimuli could reliably evoke repetitive burst firing activity, which is comparable to the rhythmic spike-burst activity of TRN neurons (5,23,24). This is an intrinsic firing pattern of TRN neurons during NREM sleep and is hypothesized to be the main factor that drives generation of sleep spindles (4,23).…”
Section: Discussionmentioning
confidence: 79%
“…Such stimuli were repeated at intervals of 7.5 s, the average interval between sleep spindles (2,4). A second stimulus protocol consisted of 200-ms-duration light flashes repeated at 1 Hz (i.e., 1-Hz protocol); these were intended to mimic slow wave responses during NREM sleep (23)(24)(25). Finally, we used a third photostimulation protocol consisting of 20-ms-duration stimuli repeated at 0.1 Hz that has been previously reported to produce thalamic bursts and cortical spindles in vivo (i.e., pulse protocol) (18).…”
Section: Resultsmentioning
confidence: 99%
“…6 gives the distribution of spike thresholds for the neurons of one rat in the case of three acupuncture frequencies. To measure threshold variation, we compute the standard deviation of each voltage threshold distribution [31,33]. It is found that the variability in spike threshold evoked by 30 times/min acupuncture (12:1179 mV, n¼ 220) is not different to the ones evoked by acupuncture with 60 times/min (11:9873 mV, n¼323) or 120 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…If it is below the threshold, the neuron remains quiescent. In many neurons, the spike threshold is not constant but dynamic, which varies with neuronal recent spiking behaviors, such as the preceding rate of depolarization, the average membrane potential, or the preceding interspike interval [27][28][29][30][31][32][33][34][35][36]. The dynamic spike threshold could be regulated by ionic channel kinetics, such as Na þ channel inactivation and K þ channel activation [27][28][29]31,32,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation